Effect of weather parameters on the seasonal dynamics of tobacco caterpillar, Spodoptera litura (Lepidoptera: Noctuidae) in castor in Telangana State - P. DURAIMURUGAN (Journal of Agrometeorology, 2021)
Field experiments were carried out for four years (2012-13 to 2015-16) to study the seasonal dynamics of tobacco caterpillar, Spodoptera litura in castor and its relationship with different weather parameters during kharif season in Telangana State. Moth catches of S. litura were observed throughout the crop season, wherein maximum catches (44.8 to 124 moths/trap/week) were observed during mid- August to late-October [33rd to 43rd Standard Meteorological Week (SMW)]. Peak oviposition (2.0 to 14.8 egg-masses/5 plants) and larval incidence (14.4 to 48 larvae/5 plants) of S. liturawas recorded during mid-August to mid-November (33rd to 46th SMW) coinciding with the vegetative to primary spike development stage of the crop. The correlation analysis indicated that the moth catches and larval population of S. litura showed significant positive correlation with weather parameters viz., maximum temperature, minimum temperature, rainfall and rainy days, while egg-masses of S. litura showed significant negative correlation with morning relative humidity and minimum temperature.The stepwise regression analysis revealed that minimum temperature, rainy days, wind speed and evening relative humidity could explain 64 per cent variation in S. litura moth catches. Among all the variables morning relative humidity was found to contribute significantly and showed 59 per cent effect on the population fluctuation of eggmasses, while rainy days and maximum temperature could explain 51 per cent variation in larval population of S. litura in castor.The models were validated with independent data 2015-16. The overall results suggested that the models can be used for predicting the population of S. litura in castor for optimizing management strategies.